Mulheres na Capoeira: resistência dentro e fora da roda - Silva, Ana Beatriz Matilde da (2019)
The Afro-Brazilian culture, for a long time was placed in a position of marginalization, being valued the Eurocentric to the detriment of other cultures. Also subject to marginalization, in a sexist society, women have struggled for time-space in spheres hitherto reserved for masculine performance and predominance. Capoeira is a social practice where women have sought recognition and appreciation. The general objective of this research was to describe and understand the educational processes unleashed in Capoeira practiced by women, understanding such processes from the historical aspects of women's struggle for space and recognition in this field. Also, as a specific objective, to know the trajectory of these women in Capoeira and to understand the choice and permanence of these women in this practice. This is a qualitative research, in which bibliographical and field research was carried out, using as data collection semi-structured interviews with four women capoeiristas from the cities of São Carlos, Campinas and Mogi Guaçu. The analysis of the collected data was made from the category system, through which three categories emerged: Family and Capoeira; How I feel like a woman in Capoeira; Capoeira that transforms. From the analysis, we consider that women, starting from the foundation of Capoeira and the demands for permanence in this space, are building a new way of being and being that expands to other spaces. This means thinking about permanent construction, in constant struggle, using ginga, mandinga, ancestry, as a strategy of struggle, body care, search for freedom and the possibility of being a woman.